Trisomy 7 mosaicism at amniocentesis: Interphase FISH, QF-PCR, and aCGH analyses on uncultured amniocytes for rapid distinguishing of true mosaicism from pseudomosaicism - Chih-Ping Chen; Hsu-Kuang Huang; Yi-Ning Su; Schu-Rern Chern; Jun-Wei Su; Chen-Chi Lee; Dai-Dyi Town; Wen-Lin Chen; Yu-Ting Chen; Wayseen Wang (Elsevier, 2012)
Objective: To present prenatal diagnosis of true trisomy 7 mosaicism. Materials, Methods and Results: A 36-year-old woman underwent amniocentesis at 18 weeks of gestation. Amniocentesis revealed a karyotype of 47,XY,+7[20]/46,XY[9]. The parental karyotypes were normal. Repeated amniocentesis was performed at 20 weeks of gestation. Array comparative genomic hybridization (aCGH) analysis on uncultured amniocytes manifested a genomic gain in chromosome 7. Quantitative fluorescent polymerase chain reaction (QF-PCR) analysis on uncultured amniocytes showed a biparental diallelic pattern with a dosage increase in the maternal allele. Interphase fluorescence in situ hybridization (FISH) on uncultured amniocytes revealed three 7q-specific signals in 13 of 50 (26%) of the cells. The cultured amniocytes had a karyotype of 47,XY,+7[12]/46,XY[14]. The ultrasound findings were unremarkable. The pregnancy was subsequently terminated, and a fetus was delivered with facial dysmorphisms. Postnatal tissue samplings revealed the mosaic trisomy 7 level of 37.5% (15/40), 30% (12/40), 42.5% (17/40), 82.5% (33/40), 52.5% (21/40), and 27.5% (11/40) in skin, liver, lungs, placenta, membrane, and cord, respectively. The cord blood had a karyotype of 46,XY. PEG1/MEST methylation-sensitive high-resolution melting PCR assay of cord blood showed no uniparental disomy for chromosome 7. Conclusion: Interphase FISH, QF-PCR, and aCGH analyses on uncultured amniocytes are useful for rapid distinguishing of true mosaicism from pseudomosaicism for trisomy 7 at amniocentesis. Cord blood sampling for confirmation of fetal trisomy 7 mosaicism is not practical.